O DESIGN VOLTADO AO PROJETO DE MESA DE ESTUDO PARA CRIANÇAS INSERIDAS NO AMBIENTE ESCOLAR - Pinto, Ana C. G.; Micheletto, Bibiana; Celuppi, Maria C.; Foresti, Teofanis (Salão do Conhecimento, 2013)
Resumo